Removal of Chemical Contaminants of Micro-Polluted Water from Wastewater Treatment Plant Through Electrochemical Oxidation - Wang, Hao; Li, Xuejin; Song, Shuangyan (Asian Journal of Chemistry, 2013)
The electrochemical oxidation was adopted to further treat secondary effluent of wastewater treatment plants. The removal effect of major pollutants of constructed wetland effluent was mainly investigated and the main chemical reaction path of the removal of organic matter and nitrogen compounds by electrochemical method was discussed preliminarily. The results showed the best removal ratio of NH3-N, total nitrogen and total phosphorus was 94.2, 82.8 and 60.5 %, respectively after dosing NaCl on the condition of different electrolysis time and constant current 5A (namely the current density 7.4 mA/cm2). Meanwhile, the effect was better than no NaCl. If other experimental conditions remained unchanged, the major pollutants were removed faster by electrolysis. Considering power consumption, it suggested that the best operation condition was of some salt solution, the current density 7.4 mA/cm2 and 0.5 h.